Eukaryotic transient-expression system based on recombinant vaccinia virus that synthesizes bacteriophage T7 RNA polymerase. - Fuerst, T R (1986)
DNA coding for bacteriophage T7 RNA polymerase was ligated to a vaccinia virus transcriptional promoter and integrated within the vaccinia virus genome. The recombinant vaccinia virus retained infectivity and stably expressed T7 RNA polymerase in mammalian cells. Target genes were constructed by inserting DNA segments that code for beta-galactosidase or chloramphenicol acetyltransferase into a plasmid with bacteriophage T7 promoter and terminator regions. When cells were infected with the recombinant vaccinia virus and transfected with plasmids containing the target genes, the latter were expressed at high levels. Chloramphenicol acetyltransferase activity was 400-600 times greater than that observed with conventional mammalian transient-expression systems regulated either by the enhancer and promoter regions of the Rous sarcoma virus long terminal repeat or by the simian virus 40 early region. The vaccinia/T7 hybrid virus forms the basis of a simple, rapid, widely applicable, and efficient mammalian expression system.